2021
DOI: 10.1073/pnas.2026246118
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 promotes noncanonical inflammasome activation through intracellular binding to lipopolysaccharide glycans

Abstract: Cytosolic lipopolysaccharides (LPSs) bind directly to caspase-4/5/11 through their lipid A moiety, inducing inflammatory caspase oligomerization and activation, which is identified as the noncanonical inflammasome pathway. Galectins, β-galactoside–binding proteins, bind to various gram-negative bacterial LPS, which display β-galactoside–containing polysaccharide chains. Galectins are mainly present intracellularly, but their interactions with cytosolic microbial glycans have not been investigated. We report th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 76 publications
0
25
0
Order By: Relevance
“…The K + efflux caused by GSDMD pores activates NLRP3 and initiates caspase1-dependent IL-1β and IL-18 maturation. Galectin-3 can augment caspase-4/11 oligomerization and promote non-canonical inflammasome activation through LPS binding [ 176 ]. Notably, Moretti et al unveiled another mechanism by which the simultaneous detection of bacterial RNA by NLRP3 and the binding of LPS by pro-caspase-11 promoted a pro-caspase-11–NLRP3 interaction that facilitated their interdependent activation [ 177 ].…”
Section: Cellular Mechanisms Driving Nlrp3 Inflammasome Activationmentioning
confidence: 99%
“…The K + efflux caused by GSDMD pores activates NLRP3 and initiates caspase1-dependent IL-1β and IL-18 maturation. Galectin-3 can augment caspase-4/11 oligomerization and promote non-canonical inflammasome activation through LPS binding [ 176 ]. Notably, Moretti et al unveiled another mechanism by which the simultaneous detection of bacterial RNA by NLRP3 and the binding of LPS by pro-caspase-11 promoted a pro-caspase-11–NLRP3 interaction that facilitated their interdependent activation [ 177 ].…”
Section: Cellular Mechanisms Driving Nlrp3 Inflammasome Activationmentioning
confidence: 99%
“…In phase 2b, this drug was safe but not associated with significant reduction in fibrosis compared with placebo except for a subgroup of patients without oesophageal varices 67 . Since LGALS3, galectin-3, has emerged as a canonical 62 and noncanonical inflammasome activator in macrophages 68 and has been found in myeloid-derived cells 23 , it is plausible that activation LGALS3 in Kupffer cells is an early event in the cascade of events taking place in the progression from hepatic simple steatosis into NASH. However, in rats, hepatic stellate cells production of galectin-3 contributes to the expansion of hepatic progenitor cells 69 .…”
Section: Discussionmentioning
confidence: 99%
“…found that Δ1-62 and Δ1-116 showed a 3- to 6-fold increased binding efficiency to asialofetuin compared to native galectin-3 when tagged with SNAP ( 140 ). Although galectin-3 enhances neutrophil activation by binding to microbial lipopolysaccharides via its carbohydrate recognition domain, N-terminal domain is also required, indicating dependence upon multivalency of galectin-3 ( 141 , 142 ).…”
Section: Discussionmentioning
confidence: 99%